Peculiarities of Postgraduate Education of the World Leading Countries and International Experience of Postgraduate Education of Law Enforcement Bodies - Artyushin, Georgiy (Pedagogical Discourse, 2013)
The article deals with the problem of postgraduate professional education, including postgraduate education of law enforcement officers. It shows the importance of postgraduate professional education for solving urgent problems of our time. The tasks that are now being solved by postgraduate education in the modern world are determined. The role of the Bologna process in the development of postgraduate professional education is shown. Questions of motivation to secondary vocational education are studied. The contents, forms of postgraduate education in the leading countries of the world are revealed. The international experience of postgraduate education of law enforcement officers is described. The objectives and guidelines of such training are determined.